Is There a Role for FDG-PET for the Assessment of Treatment Efficacy in Wilms' Tumor? A Case Report and Literature Review. (1st October 2013) - Provenzi, M.; Saettini, F.; Conter, V.; Chinaglia, D.; Vai, P.; Bruno, A.; Cavalleri, L.; Foglia, C.; Giraldi, E.; Collini, P.; Spreafico, F.
<x xml:space="preserve">Abstract</x> Background: The role of FDG-PET in Wilms' tumor has not been well established. The aim of this report is to describe the role of FDG-PET to assess chemotherapy efficacy and to show potential correlations between different Standardized Uptake Values (SUVs) and histopatological features in a patient with persisting metastatic disease. CASE description: A 3-year-old boy was diagnosed with Wilms' tumor without anaplasia. The patient underwent treatment as according to the AIEOP-TW-2003 protocol, for stage III tumors. Therapy was discontinued with no evidence of disease, yet 9 months later thorax metastases were found. Although second and third line treatments were administered, conventional imaging demonstrated stable disease. Metronomic chemotherapy as well was employed for 44 months and FDG-PET was annually performed basing on responsible local physician choice trying to better describe the disease status. Four months after fourth line treatment was stopped, the patient manifested clinical symptoms; lesions began to increase their metabolic activity inhomogeneously. Therapy was hence restarted and SUVs decreased. Metastasectomies were then performed and histology revealed a correlation between viable disease shown by higher FDG-PET uptake and viable tumor areas. Conclusions: Our case discussion demonstrates that FDG-PET is potentially valuable in Wilms' tumor correlating SUV values and histological features of the tumor after chemotherapy. This case suggests that FDG-PET is a valid tool to assess chemotherapy response in relapsed Wilms' tumor even in case of no evidence of significant dimensional changes under conventional imaging.